Scalable microwave applicators for high-temperature processing - Rodriguez Oyarzun, Jose Miguel (2019)
There have been numerous attempts to develop microwave-based processes for applications including waste treatment, metallurgy and advanced material synthesis. At a laboratory scale improvement in energy efficiency and reduction in the environmental impact for many of these applications has been demonstrated to be potentially significant. Unfortunately, very few if any applications of high-temperature microwave processes, with products reaching more than 250 °C, have ever reached a commercial scale. A multiplicity of factors have hindered such developments including a lack of understanding of microwave-material interactions and their variation during real processing conditions and also lack of consideration of material transport techniques for moving the products through the microwave heating systems and their robustness and scalability to full scale. A clear gap in the development of high-temperature microwave applications has been highlighted, with no or very few, clear scale-up strategies or hardware solutions able to meet the requirements around robustness for continuous operation and ultimately commercial implementation. In this work, three concepts have been developed which have enabled a range of scalable options for microwave applicators that can both underpin proof of concept and full-scale processes, crucially at high temperature. An elliptical cylindrical cavity applicator, a hybrid toroidal fluidised bed, and a metallic conveyor belt system are presented. All of these concepts have been developed to the prototype stage, and the design and performance have been studied by numerical simulation and validated through experimental measurements and cross-platform simulation. The simulation framework was also validated against a number of different processing systems with several test materials evidencing suitability for the design and evaluation of microwave heating systems for high-temperature application.